2019
DOI: 10.3390/v11070585
|View full text |Cite
|
Sign up to set email alerts
|

Novel Human Astroviruses: Prevalence and Association with Common Enteric Viruses in Undiagnosed Gastroenteritis Cases in Spain

Abstract: A remarkable percentage of acute gastroenteritis cases remain etiologically undiagnosed. The aim of the study was to determine the prevalence of common and emerging enteric viruses, such as novel human astroviruses, among undiagnosed samples from children with acute gastroenteritis. Epidemiological studies for novel human astroviruses are still scarce. Stool samples collected over two consecutive winter seasons (2016–2017) from children with gastroenteritis in Spain, which were negative for bacteria, rotavirus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 39 publications
3
19
1
Order By: Relevance
“…While Holtz et al did not find any association between MLB1 infection and diarrhea 28 , Meyer et al reported an association between MLB1 and diarrhea and between MLB3 and asymptomatic disease, and no significant association of VA viruses with any of the groups 27 . The results of the present study are also in agreement with the high rate of co-infections observed in our previous study: MLB and VA were identified in co-infection with ≥1 other enteric virus in 78% and 54.8% of cases (all symptomatic), respectively, raising the question of their contribution to the digestive tract symptoms 29 . In this previous study, we could not observe a difference in the novel HAstV mean viral RNA titer during mono-and co-infection.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…While Holtz et al did not find any association between MLB1 infection and diarrhea 28 , Meyer et al reported an association between MLB1 and diarrhea and between MLB3 and asymptomatic disease, and no significant association of VA viruses with any of the groups 27 . The results of the present study are also in agreement with the high rate of co-infections observed in our previous study: MLB and VA were identified in co-infection with ≥1 other enteric virus in 78% and 54.8% of cases (all symptomatic), respectively, raising the question of their contribution to the digestive tract symptoms 29 . In this previous study, we could not observe a difference in the novel HAstV mean viral RNA titer during mono-and co-infection.…”
Section: Discussionsupporting
confidence: 93%
“…We found that 6.3% of case patients were positive for one or several novel HAstV. This is slightly lower than our previous study, which investigated a similar Spanish pediatric population, with a positivity rate of 10% 29 . The difference can be explained by the study period: our first study focused on two consecutive winter seasons from January-April 2016 and January-April 2017, respectively, while the present one extended over a 10-months period (August 2017-May 2018).…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations